Being a Good University Teacher: Perspective of Program Directors and Teachers Themselves - Rosa Orellana-Fernández; Eugenio Merellano-Navarro; Alejandro Almonacid-Fierro (Revista Electrónica Educare)
This research article represents a prolongation of the case study on the perception of a good university teacher from the perspective of the Education Faculty students at Universidad Autónoma de Chile (Autonomous University of Chile), Talca. It intends to contribute with a different understanding of the phenomenon from the perspective of the actors involved. This second part of the research aims to disclose the characteristics of a good University Teacher according to the opinion of the teachers themselves and administrators belonging to that Faculty. The methodology in approach adopted consisted of a qualitative one as well as of a case study. Through a process of categorization and codification, four characteristic dimensions of analysis were obtained: human, ideological, technical-pedagogical and professional-institutional. It is concluded that a good University Teacher has mainly ethical, moral and affective features that structure the interactions with the students’ community. Concerning the main attributes of quality teaching, the permanent curiosity, search for knowledge, and dialogue between the different forms of it are recognized. Technical-pedagogical characteristics that appear in this research as the methodological adaptation of teaching and evaluation emerge as secondary aspects when it comes to qualifying a good University Teacher.